1988
DOI: 10.1007/bf01310822
|View full text |Cite
|
Sign up to set email alerts
|

Biological and pathological consequences of feline infectious peritonitis virus infection in the cheetah

Abstract: An epizootic of feline infectious peritonitis in a captive cheetah population during 1982-1983 served to focus attention on the susceptibility of the cheetah (Acinoyx jubatus) to infectious disease. Subsequent observations based upon seroepidemiological surveys and electron microscopy of fecal material verified that cheetahs were indeed capable of being infected by coronaviruses, which were antigenically related to coronaviruses affecting domestic cats, i.e. feline infectious peritonitis virus/feline enteric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 56 publications
0
60
0
Order By: Relevance
“…It is likely that FCoV mutations occur regularly but the probability of emergence of FIP depends on cat density as well as underlying comorbidity (e.g., feline immunodeficiency virus infection) that encourages high viral loads in an individual or population. Mortality from FIP has been reported in nondomestic cats such as cheetahs (Acinonyx jubatus), and is partially attributed in that case to high homozygosity in the host and an inferred lack of population resistance (Evermann et al, 1988). Given the biology and pathogenesis of FCoV and FIP virus in large felids, we would expect FCoV to be most common in high-density populations or those with common mountain lion-domestic cat interactions, and FIP to occur sporadically.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that FCoV mutations occur regularly but the probability of emergence of FIP depends on cat density as well as underlying comorbidity (e.g., feline immunodeficiency virus infection) that encourages high viral loads in an individual or population. Mortality from FIP has been reported in nondomestic cats such as cheetahs (Acinonyx jubatus), and is partially attributed in that case to high homozygosity in the host and an inferred lack of population resistance (Evermann et al, 1988). Given the biology and pathogenesis of FCoV and FIP virus in large felids, we would expect FCoV to be most common in high-density populations or those with common mountain lion-domestic cat interactions, and FIP to occur sporadically.…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence of FIP among purebred cats (Scott, 1991), cheetahs (Evermann et al, 1988) and cats from FIP-susceptible bloodlines may be an indication for a genetic predisposition.…”
Section: Introductionmentioning
confidence: 99%
“…2001). It has been suggested that species exhibiting low MHC variation might have a higher susceptibility to infectious disease (Evermann et al . 1988; Mikko et al .…”
Section: Introductionmentioning
confidence: 99%